Output controllability of the discrete-time linear switched systems. (August 2016) - Babiarz, Artur; Czornik, Adam; Niezabitowski, Michał
Abstract: The article concerns the output controllability of discrete-time linear switched systems. The primary objective is to find a control signal which performs system from any initial state to the given output value in a finite time interval regardless of the switching signal. In addition, the search control signal is performed on the assumption that the current value of control is independent of the future values of switching signal. Furthermore, it is supposed that the switching sequence is constrained because some switches are not allowed. Necessary and sufficient conditions of some kinds of output controllability are presented. Consequently, three types of output controllability: from zero initial state to any final output, from any initial state to zero final output and from any initial state to any final output are discussed. Finally, illustrative examples are shown.